The relationship between knowledge levels and the use of soursop leaf tea among housewives with hypertension in the village of suku Sara Tangke - Saipullah Saipullah; Andi Pratama Putra; Muzaffar Muzaffar; Rahmiati Tagore Putri; Maulina Iriyanti (Institute of Computer Science (IOCS), 2026)
Hypertension remains a major global health problem due to its increasing prevalence and risk of serious complications. In addition to pharmacological treatment, health promotion efforts are needed to improve community awareness and encourage the use of safe complementary therapies. Soursop leaf tea (Annona muricata L.) has been widely recognized as a traditional herbal remedy; however, evidence regarding the effectiveness of educational interventions in promoting its utilization among hypertensive individuals remains limited. This study aimed to evaluate changes in knowledge and utilization of soursop leaf tea among hypertensive housewives in Suku Sara Tangke Village following a health education intervention. A one-group pretest–posttest pre-experimental design was employed from June to November 2025. A total of 46 respondents were selected through purposive sampling. Data were collected using a structured questionnaire and analyzed using the Wilcoxon signed-rank test. The findings demonstrated significant improvements in respondents’ knowledge and utilization of soursop leaf tea after the educational intervention. The obtained p-value of 0.000 (p < 0.05) indicates that the intervention was not only statistically significant but also practically meaningful in encouraging positive behavioral changes toward the adoption of herbal-based complementary therapy for hypertension management. The novelty of this study lies in integrating community-based health education with local herbal resources, highlighting the potential of soursop leaf tea utilization as a culturally relevant health promotion strategy among hypertensive housewives. These findings suggest that educational approaches can effectively support the acceptance and utilization of traditional herbal therapies within community health promotion programs.